Effective engagement of the Native Fish Strategy is delivered by coordinated and contextual effort. (March 2014) - Hames, Fern; Townsend, Anthony; Ringwood, Greg; Clunie, Pam; McPhail, Jonathan
Abstract : Key distinguishing features of the Native Fish Strategy were genuine, targeted partnerships and effective, planned engagement that aimed to inform, involve and empower relevant stakeholders. Engagement programmes were developed and coordinated at a Basin‐wide scale, but diverse engagement activities were adapted and implemented in a local context by dedicated coordinators.